The Effectiveness of LENTERA-Based Interactive Media on Early Childhood Scientific Literacy: Learning Engagement as a Covariate - Ni Luh Ika Windayani; Ni Wayan Risna Dewi; Ni Putu Widyasanti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Scientific literacy is a fundamental competence that should be developed from early childhood. However, early childhood learning practices remain predominantly teacher-centered, minimally exploratory, and supported by static media, resulting in suboptimal learning engagement and scientific literacy outcomes. This study aimed to examine the effectiveness of LENTERA (Literacy and Research Exploration in Learning) based interactive media on early childhood students’ scientific literacy, with learning engagement as a covariate. The media is a digital learning application that integrates illustrated stories, animated videos, observation activities, simple experiments, interactive quizzes, and reflection worksheets designed according to the stages of literacy, exploration, investigation, analysis, and reporting. A quasi-experimental design with a single-factor independent group and a covariate was employed. The participants were 64 early childhood education students randomly assigned to an experimental group and a control group. Data were collected using a scientific literacy test and a learning engagement observation sheet. Data were analyzed using descriptive statistics and ANCOVA after satisfying the assumptions of normality, homogeneity, linearity, and homogeneity of regression slopes. The findings revealed a significant difference between groups after controlling for learning engagement (F(1,61)=5.759, p=0.019, ηp²=0.086), with the experimental group achieving higher adjusted mean scores. Learning engagement also significantly affected scientific literacy (F(1,61)=33.157, p<0.001, ηp²=0.352). The study concludes that LENTERA-based interactive media is effective in enhancing early childhood students’ scientific literacy and learning engagement.